Petrushka in the Theatre for Children in the First Ten Years After the October Revolution (Two Plays by S.I. Marshak) - Svetlana P. Sorokina (Studia Litterarum, 2018)
Samuil Marshak came to Ekaterinodar in 1918 and became the leader of the Department for children’s orphanages and colonies in 1920. In July 1920, he assisted and promoted the foundation of the professional theatre for children. He favored children’s improvisation, use of theatrical conventionality, and group work. The same principles were at the basis of the Petrushka theatre; therefore, Marshak’s turn to folklore theatre was a natural outcome of his previous work. Marshak wrote his first play Petrushka in 1921 upon meeting a popular folklore artist I. Zaitsev. In his play, Marshak attempted to make an emphasis on improvisation that was typical for folklore theatre, for example, encouraging performers to cross a boundary between the stage and the audience. These principles persevered in the staging of the play. Marshak thus naturally combined formulas and plot elements of folklore theatre with those of his own art. He was among those writers who tried to adapt Petrushka theatre for children. The plot and structure of the next play — Petrushka the Foreigner (1927) — were not as dependent on the folklore play as the previous one. Marshak builds the plot as a chain of events, gets rid of traditional folklore characters (except Petrushka), and substitutes the latter with contemporary characters that reflected new social reality. Petrushka as a character also undergoes changes. He is no longer a conventional character without social background and age but a mischievous little boy and urchin. Verbal structure of this play no longer bears on the verbal structure of the folklore play as before. Thus, the essay concludes that Marshak “Petrushka” plays illustrated the main trends of the folklore adaptation for children during the first ten years after the October revolution.